Nutrigenomics and public health - Getz, Jean; Adhikari, Koushik; Medeiros, Denis M. (My University, 2010)
Nutrigenomic research may uncover the keys to utilizing genetic information to create food products that improve public health through mitigation of chronic diseases.
Keywords: Nutrigenomics; Functional foods; Chronic disease; Public health; Food processing; Gene regulation